Revealing the Existence of “Pantauan Lebaran” Customs in the Midst of Social Changes in Modern Society in Ribang Kemambang, Lahat Regency, South Sumatra Province - Fitri Oviyanti; Maryamah Maryamah; Era Afriza; Uswatun Hasanah; Hafizh Maulana Nugraha (Academia Open, 2025)
General Background: Cultural traditions such as Pantauan Lebaran play a central role in shaping Indonesia’s communal identity. Specific Background: In Ribang Kemambang, Lahat Regency, this Eid al-Fitr visitation ritual persists amid accelerating modernization and digital transformation. Knowledge Gap: However, limited studies examine how this customary practice adapts to contemporary social changes while retaining its moral and cultural essence. Aim: This study investigates the current form, meanings, and adaptive strategies of Pantauan Lebaran as a dynamic cultural system. Results: Using qualitative ethnographic methods, the study finds that the ritual strengthens social cohesion, reinforces Islamic values such as silaturahmi and birrul walidain, and remains resilient through mechanisms like digital coordination, youth involvement, and flexible implementation. Novelty: The research reveals Pantauan Lebaran as a glocalized cultural practice where local wisdom and global modernity coexist, demonstrating reflexive cultural transformation rather than decline. Implications: These findings highlight the community’s capacity to preserve cultural identity while engaging with modern social realities, offering insights for cultural sustainability, Islamic educational development, and policy frameworks supporting local traditions in the digital era. Highlights: Shows how Pantauan Lebaran adapts to modernization while preserving core religious–cultural values Demonstrates youth and digital media as key drivers in sustaining and transforming the tradition Positions Pantauan Lebaran as a model of glocalization and cultural resilience in rural Indonesian society. Keywords: Pantauan Lebaran, Cultural Resilience, Glocalization, Islamic Educational Values, Social Cohesion